Nitrogen Balance in Rats Fed Rices Differing in Protein Content - Eggum, Bjørn O.; Juliano, Bienvenido O. (Wiley, 1973)
Nitrogen balance was studied in rats fed seven milled rice samples with 1.10 to 2.73% N dry basis. True digestibility (t.d.) of the protein ranged from 94.4 to 100.1%, biological value (b.v.) ranged from 67.9 to 75.2% and net protein utilisation (n.p.u.) from 64.2 to 75.3%. T.d. and n.p.u. were positively correlated with lysine content of rice protein (3.17 to 4.07 g/16 g of N). Utilisable N ranged from 0.83 to 1.81% and was mainly determined by N content of milled rice (r = 0.988**). A sample of brown rice had lower t.d. but higher b.v. than the corresponding milled rice. Digestibility of amino acids of milled rice protein by fae al analysis ranged from 94.1 to 100.0% in samples with 1.38 and 2.74% N dry basis.